2011
DOI: 10.3851/imp1726
|View full text |Cite
|
Sign up to set email alerts
|

On-Treatment Monitoring of Liver Fibrosis with Transient Elastography in Chronic Hepatitis B Patients

Abstract: LSM could predict advanced fibrosis during antiviral therapy according to the ALT-based algorithm. Decrease in absolute LSM value, which could be related to ALT normalization, was unreliable to indicate regression of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 29 publications
(43 reference statements)
3
82
2
Order By: Relevance
“…In particular, high ALT level contributes to increased liver stiffness. After ALT normalization with antiviral therapy, the liver stiffness typically declines even without regression of fibrosis [86]. Whether the on-treatment liver stiffness remains robust in prognostication is currently unclear.…”
Section: Diagnosis Of Cirrhosis As the Achilles Heelmentioning
confidence: 98%
“…In particular, high ALT level contributes to increased liver stiffness. After ALT normalization with antiviral therapy, the liver stiffness typically declines even without regression of fibrosis [86]. Whether the on-treatment liver stiffness remains robust in prognostication is currently unclear.…”
Section: Diagnosis Of Cirrhosis As the Achilles Heelmentioning
confidence: 98%
“…This may be due to the fact that patients without liver cirrhosis had a better liver condition than those in group 1 when they were enrolled and their hepatic histological changes are based on necroinflammation. Wong et al (15) prospectively studied patients with CHB undergoing liver biopsy twice before and at week 48 of antiviral treatment, revealing a significant decrease of the metavir fibrosis score, while the metavir activity score showed no significant change.…”
Section: Discussionmentioning
confidence: 99%
“…Significant histologic improvements have been documented in studies of paired liver biopsies from patients with chronic hepatitis C who achieved sustained viral eradication (Poynard et al 2002;Shiratori et al 2000) and patients with chronic hepatitis B who received long-term antiviral therapy (Chang et al 2010;Hadziyannis et al 2006). Several studies reported a significant decrease in liver stiffness values, compared with baseline values, in patients with HCV who achieved sustained viral eradication (Fontana et al 2009;Hezode et al 2011;Martinez et al 2011b;Ogawa et al 2009;Vergniol et al 2009;Stasi et al 2013;Casado et al 2013), as well as in HBV-infected patients treated with nucleoside analog drugs (Enomoto et al 2010;Fung et al 2011b;Lim et al 2011;Ogawa et al 2011;Osakabe et al 2011;Wong et al 2011;Kim et al 2013;Kuo et al 2014).…”
mentioning
confidence: 93%